The renal consequences of maternal obesity in offspring are overwhelmed by postnatal high fat diet. - Sarah J Glastras; Hui Chen; Michael Tsang; Rachel Teh; Rachel T McGrath; Amgad Zaky; Jason Chen; Muh Geot Wong; Carol A Pollock; Sonia Saad (PLoS ONE, 2017)
AIMS/HYPOTHESIS:Developmental programming induced by maternal obesity influences the development of chronic disease in offspring. In the present study, we aimed to determine whether maternal obesity exaggerates obesity-related kidney disease. METHODS:Female C57BL/6 mice were fed high-fat diet (HFD) for six weeks prior to mating, during gestation and lactation. Male offspring were weaned to normal chow or HFD. At postnatal Week 8, HFD-fed offspring were administered one dose streptozotocin (STZ, 100 mg/kg i.p.) or vehicle control. Metabolic parameters and renal functional and structural changes were observed at postnatal Week 32. RESULTS:HFD-fed offspring had increased adiposity, glucose intolerance and hyperlipidaemia, associated with increased albuminuria and serum creatinine levels. Their kidneys displayed structural changes with increased levels of fibrotic, inflammatory and oxidative stress markers. STZ administration did not potentiate the renal effects of HFD. Though maternal obesity had a sustained effect on serum creatinine and oxidative stress markers in lean offspring, the renal consequences of maternal obesity were overwhelmed by the powerful effect of diet-induced obesity. CONCLUSION:Maternal obesity portends significant risks for metabolic and renal health in adult offspring. However, diet-induced obesity is an overwhelming and potent stimulus for the development of CKD that is not potentiated by maternal obesity.